Forensic Linguistic Examination of Illocutionary Acts in the Police BAP of the “EN” Murder Case in Muara Bungo - Rini Afrilesa Jasmir; Vera Magria (Fakultas Sastra Universitas Ekasakti, 2025)
This study examines the illocutionary acts embedded in the police interrogation transcript (Berita Acara Pemeriksaan/BAP) of WD, the suspect in the murder of EN in Muara Bungo. Using Searle’s taxonomy of speech acts, the research identifies assertives, directives, expressives, and commissives as the dominant forms shaping the interaction between the interrogator and the suspect. The analysis reveals that the interrogator consistently relies on high-pressure directives that control narrative flow, restrict the suspect’s discursive freedom, and guide the production of legally relevant information. In contrast, the suspect’s responses exhibit a pattern of assertive confessions, mitigation strategies through reported speech, emotional expressions, and moral positioning. These linguistic choices not only construct his version of events but also function as strategic attempts to negotiate responsibility and reshape the legal interpretation of his actions. The findings indicate that BAP statements are not neutral reflections of spoken interaction but structured linguistic events influenced by institutional power, psychological dynamics, and communicative strategies. This study highlights the importance of forensic linguistic analysis in evaluating the credibility, voluntariness, and evidentiary value of interrogation transcripts in Indonesian legal settings. It also contributes to understanding how language functions as both evidence and a tool for shaping legal realities.